2019
DOI: 10.1007/s10973-019-08415-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiation and magnetic field on mixed convection stagnation-point flow over a cylinder in a porous medium under local thermal non-equilibrium

Abstract: Heat transfer enhancement and entropy generation are investigated in a nanofluid, stagnation-point flow over a cylinder embedded in a porous medium. The external surface of cylinder includes non-uniform transpiration. A semi-similarity technique is employed to numerically solve the three-dimensional momentum equations and two-equation model of transport of thermal energy for the flow and heat transfer in porous media. The mathematical model considers nonlinear thermal radiation, magnetohydrodynamics, mixed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 47 publications
(81 reference statements)
1
20
0
Order By: Relevance
“…The latter implies that the velocity of the fluid and solid particles is the same without any slip velocity. Boussinesq approximation is used to calculate the fluid density as a function of temperature [26,27].…”
Section: Problem Configuration and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter implies that the velocity of the fluid and solid particles is the same without any slip velocity. Boussinesq approximation is used to calculate the fluid density as a function of temperature [26,27].…”
Section: Problem Configuration and Boundary Conditionsmentioning
confidence: 99%
“…Four mesh sizes of 40 × 120, 50 × 150, 60 × 180 and 70 × 210 on the x-y domain were examined. The nondimensional temperature versus time at the midpoint of the (27) enclosure, located at x * = y * = 0.5 , is presented in Fig. 4 for various mesh sizes.…”
Section: Grid Independencymentioning
confidence: 99%
“…To calculate the local rate of entropy generation the velocity, temperature and concentration equations are incorporated into the equations of volumetric local entropy generation given in Refs. [45,[49][50][51][52].…”
Section: Solutions Of Momentum Energy and Mass Transfer Equationsmentioning
confidence: 99%
“…In their study, the dual solutions are obtained only in opposing flow. Alizadeh et al [19] examined the impact of radiation and electromagnetic field in a mixed convection stagnation-point flow surrounding a cylinder. It is concluded that the radiative system produces a higher Nusselt number and less thermal irreversibilities.…”
Section: Introductionmentioning
confidence: 99%